Fertility Treatment in India: A Cost Optimization Approach for Making Fertility Treatment Affordable - Kandari, Pradeep Singh (Digital Repository of Theses, 2024)
Infertility is a reality for more than 15% of couples globally. In India, only a fraction can access tertiary level care with specialty hospitals catering to couples. A large private segment has emerged in India and affordability has become a constant factor in allowing patients to access care with acceptable success rates of 40% average per cycle. Our Quantitative research work has surveyed 80 (eighty) experts in the field nationally and a Panel of experts has been consulted to provide a detailed quantitative estimate of cost optimization methods in Fertility treatment. This work is seminal in nature and is the first of its kind in India where government support and research work is scant on cost optimization for Fertility Centers in India. The results and discussions fore with can be used to build more robust operations and improve access to care to aspiring couples.